Program Bantuan Rumah Tidak Layak Huni: Pengembangan Ekonomi Islam Pada Masyarakat di Desa Ringinanom - Budiyarsih Budiyarsih; Ahmad Bayu; Siti Khoiriyah; Milna Wafirah (Fakultas Ekonomi dan Bisnis Islam IAINU Kebumen, 2021)
Economic growth is the most important part of economic policy in a country or any economic system. This study aims to determine the development of the Islamic economy through the assistance of Uninhabitable Houses (RTLH). The method used in this research is a qualitative method. The number of community economic activities becomes the greatest potential to develop economic potential, therefore development is carried out openly and follows government regulations. Regional economic development refers to the main objective, to increase the number and variety of job opportunities for the local community. As an effort to increase Islamic economic development, the Ringinanom Village government distributed stimulus assistance for Uninhabitable Houses (RTLH) using the five basic principles of Islamic economics.